Effects of Early Mobilization on Hemodynamics and Pain after Coronary Artery Bypass Graft Surgery: A Randomized Controlled Trial - Sevda Jalili; Atefeh Allahbakhshian; Azizeh Farshbaf Khalili; Khorshid Mobasseri (Journal of Caring Sciences)
Introduction: Patients with coronary artery disease (CAD) can improve quality of life by undergoing coronary artery bypass graft (CABG), but they may face various complications. Early mobilization can help prevent these complications. This study aimed to evaluate the effects of two early mobilization protocols on pain and hemodynamic outcomes in patients who had CABG surgery. Methods: This was a randomized, blinded clinical trial with a three-arm parallel design, conducted on 105 patients who underwent CABG at Shahid Madani hospital in Tabriz. The patients were randomly assigned to three groups: control, first intervention, and second intervention. The control group received standard care, while two intervention groups received early mobilization based on passive and active range of motion (ROM) activities and early mobilization based on deep breathing exercises respectively. Data were collected using a questionnaire that measured pain intensity using a facial pain scale and hemodynamic indicators using a monitor device. Data analysis was performed using SPSS version 24 software and descriptive and inferential statistics methods. Results: According to the study, the second intervention group is more effective than the first intervention group. The results indicated that in both morning and evening shifts, the mean of systolic blood pressure (SBP) increased significantly in three groups. Also, the mean of diastolic blood pressure (DBP) increased significantly in both shifts in intervention group 1 and control. The mean of DBP decreased (MD=-26.0, 95% CI: -5.6 to -1.2; P=0.003) significantly among intervention group 2 compared to control group in the evening. The results also indicated that the mean of heart rate (HR) raised significantly in both shifts in all three groups. In the morning, there was a significant difference between intervention group 2 and 1 compared to control. The mean of arterial oxygen saturation was a significant difference between intervention group 2 and intervention group 1 and control group in the both shifts. The mean of pain decreased significantly in the morning in two intervention groups. Similarly, in the evening, the mean of pain decreased significantly in intervention group 1, and intervention group 2. Both in the morning and evening, there was a significant difference between intervention group 2 and intervention group 1 (P<0.001). Conclusion: This study provides valuable insights into the effects of early mobilization interventions on patients after CABG, but more research is needed to determine the optimal timing and intensity of mobilization protocols for patients after CABG and to explore the long-term effects and cost-effectiveness of these interventions.